Degradation and characterization of resorbable phosphate-based glass thin-film coatings applied by radio-frequency magnetron sputtering - Stuart, Bryan; Gimeno-Fabra, Miquel; Segal, Joel; Ahmed, Ifty; Grant, David M. (American Chemical Society, 2015)
Quinternary phosphate-based glasses of up to 2.67 μm, deposited by radio-frequency magnetron sputtering, were degraded in distilled water and phosphate-buffered saline (PBS) to investigate their degradation characteristics. Magnetron- sputtered coatings have been structurally compared to their compositionally equivalent melt-quenched bulk glass counterparts. The coatings were found to have structurally variable surfaces to melt-quenched glass such that the respective bridging oxygen to nonbridging oxygen bonds were 34.2% to 65.8% versus 20.5% to 79.5%, forming metaphosphate (PO3)−(Q2) versus less soluble (P2O7)4− (Q1) and (PO4)3− (Q0), respectively. This factor led to highly soluble coatings, exhibiting a t1/2 degradation dependence in the first 2 h in distilled water, followed by a more characteristic linear profile because the subsequent layers were less soluble. Degradation was observed to preferentially occur, forming voids characteristic of pitting corrosion, which was confirmed by the use of a focused ion beam. Coating degradation in PBS precipitated a (PO3)−metaphosphate, an X-ray amorphous layer, which remained adherent to the substrate and seemingly formed a protective diffusion barrier, which inhibited further coating degradation. The implications are that while compositionally similar, sputter-deposited coatings and melt-quenched glasses are structurally dissimilar, most notably, with regard to the surface layer. This factor has been attributed to surface etching of the as-deposited coating layer during deposition and variation in the thermal history between the processes of magnetron sputtering and melt quenching.